Microbiological characteristics of goat’s milk kefir with the addition of mangosteen (Garcinia mangostana L.) peel extract - listya purnamasari; Defi S. Cahyaningrum; Mochammad S. Sunarno; Viagian Pastawan; Epi Tauik (Hasanuddin University Food Science and Technology Study Program, 2020)
Kefir is one of the fermented milk products. The addition of mangosteen peel extract as a source of antioxidant was aimed to increase the functionality of fermented milk products. The purpose of this research was to study the microbiological characteristics of goat’s milk kefir addition with different concentration (0%, 1%, 2%, and 3%) of mangosteen peel extract. The extract of mangosteen peel was purchased from PT. Haldin Pacific Semesta. The results showed that the addition of mangosteen peel extract did not affect significantly on total lactic bacteria, total plate count, and total coliform, but it affected significantly on total mold and yeast. Total lactic acid bacteria in kefir decreased from kefir grain and bulk starter of kefir, but those populations still same with the standard of microorganisms in prebiotic which is 107 CFU/ml. The conclusion of this study, mangosteen peel extract can be used to decrease total microbial such as mold/yeast at concentration 3% dan 4%.